Isolasi Dan Karakterisasi Bakteri Selulolitik Dari Tanah Hutan Mahoni di Kabupaten Timor Tengah Selatan Nusa Tenggara Timur - Mau, Anastasia Nio; Missa, Hildegardis; Djalo, Aloysius; Nau, Getrudis Wilhelmina; Sepe, Florentina Yasinta (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
The utilization of lignocellulosic biomass as an alternative energy source and industrial material is still constrained by the limited availability of efficient cellulase-producing microorganisms. Mahogany forest soil, which contains leaf litter rich in cellulose, has the potential to serve as a habitat for cellulolytic bacteria with unique characteristics. This study aimed to isolate and characterize cellulolytic bacteria from mahogany forest soil in South Central Timor Regency, East Nusa Tenggara. The research employed an exploratory laboratory design with purposive sampling to collect soil samples beneath mahogany leaf litter at a depth of 0–20 cm. Bacterial isolation was conducted using the serial dilution method and cultivation on Carboxy Methyl Cellulose (CMC) medium. Characterization was performed based on colony morphology and Gram staining, while cellulolytic activity was assessed using the Congo Red method. Data were analyzed descriptively and quantitatively through colony counts using the plate count method and the determination of cellulolytic index values. The results revealed two bacterial isolates, namely AT1 (Gram-positive bacillus) and AT2 (Gram-positive coccus). Both isolates were able to produce clear zones, with cellulolytic indices of 1.96 and 1.26 mm, respectively. Isolate AT1 exhibited higher potential as a cellulase-producing bacterium. These findings highlight the potential of local cellulolytic bacteria as a promising source of cellulase enzymes for biotechnological applications.